Persepsi Etika Atas Tax Evasion Dan Tax Avoidance BagiWajib Pajak Orang Pribadi Di Sukoharjo - Anisa Hardianingrum; Juliati Juliati (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2020)
This research aims to examine differences in ethical perceptions of tax evasion and tax evasion for employee and non-employee taxpayers who are subjected to a self-assessment and withholding tax collection system in the Sukoharjo region. This research adopted Putri's study (2015). Objectives and areas of observation differ from Putri's research (2015). The research sample is taken with a purposive sampling technique, the sample (respondent) are selected with the criteria as an individual taxpayer whose tax collection system is a self assessment for non-employees or withholding for employees. The total sample in this study were 100 respondents. Data is taken by distributing questionnaires to selected respondents. The research method is conducted with descriptive quantitative statistics. The hypothesis is analyzed with the Mann Whitney test because the data obtained are not normally distributed in the Shapiro Wilk normality test. The results of the study revealed a difference between ethical perceptions of tax evasion and tax avoidance for employees and non-employees taxpayers.